The United States Food and Drug Administration (FDA) regulatory response to combat neglected tropical diseases (NTDs): A review. - Sanjana Mukherjee (Public Library of Science (PLoS), 2023)
The availability and accessibility of safe and effective drugs, vaccines, and diagnostics are essential to reducing the immense global burden of neglected tropical diseases (NTDs). National regulatory authorities, such as the United States Food and Drug Administration (FDA), play an essential role in this effort to ensure access to safe and effective medical products by working within a set of legal frameworks and regulatory functions. However, medical product development for NTDs remains neglected, as combating NTDs is not a viable commercial market for pharmaceutical companies. To spur research and development (R&D) of NTD products, the US government has authorized various programs and policies to engage pharmaceutical companies, many of which provide FDA with the legal authority to implement NTD programs and pathways. Thus, this review provides a clear overview of the various regulatory pathways and programs employed by the FDA to increase the availability of NTD drugs, vaccines, and diagnostics. The review assesses the available information on various regulatory considerations and their impact on NTD product development as a first step in estimating the importance of such programs. Next, findings related to currently approved NTD products through these programs are discussed. Lastly, gaps in NTD R&D are identified and suggestions on how to address these are presented. The available data shows that while such incentive programs are factored into companies' decisions to pursue NTD R&D, approved products for NTDs remains vastly insufficient. Most approved products that utilize these NTD regulatory pathways and programs are overwhelmingly for tuberculosis and malaria-both of which are not considered NTDs by the World Health Organization (WHO). Dedicated efforts are needed to facilitate and accelerate NTD product including employing multiple incentive programs, regular assessment of such programs, and leveraging on public-private partnerships.